Harnessing ai in language learning: student purposes and metacognitive strategies in a Malaysian University - Mohd Ramli, Nor Fazlin; Rusli, Rusreena; Tazijan, Farina; Zakaria, Siti Fauziana; Mahmud, Malissa Maria (GADING Journal for the Social Sciences, 2024)
Artificial Intelligence (AI) has become a household name. In education, the use of AI is being debated on the extent AI should be allowed to be integrated in the academic world. In language learning, some may argue that AI if applied wisely can lead to enhanced understanding of reading text and assisted writing process but at the same time lacks originality. However, using AI, especially among students, requires them to be critical and aware of the existence of bias and inaccuracy of information gained. Hence, this study is aimed to identify the purpose of language students using AI and the use of metacognitive strategies when using AI. The study also further seeks to identify the relationship among the identified strategies. A total of 241 respondents from an English Language undergraduate programme of a local university in Malaysia participated in the study by answering a survey. It was found that the main purpose of using AI is to complete their assignments in terms of brainstorming. The main metacognitive strategy was ‘Searching other references.’ There was also no significant difference among the metacognitive strategies used and between male and female students. This study highlights the importance of strategy awareness among the students so that they can harness the benefits of using AI in their everyday academic life.